1987
DOI: 10.1111/j.1749-6632.1987.tb36225.x
|View full text |Cite
|
Sign up to set email alerts
|

The Major Affective Disorder in Anorexia Nervosa and Bulimia

Abstract: In recent years, several lines of evidence have emerged suggesting that eating disorders in general, and bulimia in particular, are in some way linked to the major affective disorder. ' Studies, however, on the phenomenological relationship between the two illnesses have shown inconsistent results, which might be partly due to the heterogeneity of eating disorders and shortcomings of a diagnostic assessment of affective disorders. We looked for depressive syndromes in subtypes of eating disorders using standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 2 publications
4
18
1
3
Order By: Relevance
“…Considering the co-occurrence of EDs and obsessive-compulsive behaviours, the latter have been observed especially in subjects with AN [82,85,92] .…”
Section: Obsessive-compulsive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the co-occurrence of EDs and obsessive-compulsive behaviours, the latter have been observed especially in subjects with AN [82,85,92] .…”
Section: Obsessive-compulsive Symptomsmentioning
confidence: 99%
“…Obsessive-compulsive symptoms have been related to EDs and SIBs have been divided into impulsive and compulsive SIBs ( table 4 ) [25,27,28,[81][82][83][84][85][86][87][88][89][90][91][92][93] . Considering the co-occurrence of EDs and obsessive-compulsive behaviours, the latter have been observed especially in subjects with AN [82,85,92] .…”
Section: Obsessive-compulsive Symptomsmentioning
confidence: 99%
“…High rates of comorbidity between eating disorders and major depressive disorder (MDD) have been identified in numerous studies. [12][13][14][15][16][17][18][19] However, much less is known about depression during pregnancy and the postpartum period among women with eating disorders. In addition, some women have reported that their eat-ing disorders began in the postpartum period, as they attempted to lose weight gained during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Diese Form der Patientenrekrutierung ist für die Therapieforschung, die zunächst auf den Nachweis der Wirksamkeit einer bestimmten Behandlungsform abzielt, sicherlich sinnvoll und notwendig. Da inzwischen in kontrollierten Therapiestudien zahlreiche Wirksamkeitsbelege für eine manualbasierte, kognitiv-behaviorale Therapie von Patientinnen mit BN gewonnen wurden, kann und sollte sich die weitere Forschung nun aber der Frage zuwenden, ob die Befunde auf die Psychotherapie in der Praxis übertragen werden können [Wilson, 1999] [Beebe, 1994;Brewerton et al, 1995;Bulik, 1987a;Laessle et al, 1987]. Die depressiven Störungen können eine Folge der Essstörung sein [z.B.…”
Section: Hintergrundunclassified